Penerapan Analisis Diskriminan dalam Pembedaan Kelas Umur Tegakan Pinus - P Priyanto (Jurnal Manajemen Hutan Tropika, 2007)
This  study  describes the use of discriminant anylisis for pine (Pinus spp.) stand class age distinction.  Aim of this  study were (1) to arrange stand age class based on variable of aerial photograph by non hierarchy cluster analysis, and (2) to find out aerial photograph variable contribute to stand age class distinction by discriminant analysis.  Data used in study was taken from a research conducted by Adi (1998).   Pinus stand was located in KPH Bandung Utara, West Java. The variable of aerial photograph that used in this analysis were tone, shape, texture, topography, pattern, crown, diameter and height. The result showed that validation analysis of discriminant function was significant. Therefore, this function was applicable for grouping new object to stand age class based on discriminant score.